Community Participation Program in Forest and Land Rehabilitation in the Batutegi Forest Management Unit (Journal of Sylva Indonesiana, 2022)
Restoration of critical land so that its products can increase and contribute to the community's welfare is a special challenge at this time. One of the efforts made by the government in overcoming this problem is by carrying out Forest and Land Rehabilitation activities by involving farmers as local workers. This study analyses community participation in forest and land rehabilitation programs in Datar Lebuay Village, Air Naningan District, Tanggamus Regency. The research was conducted in June 2021. Data collection was carried out through interviews, observation, and documentation techniques. Respondents were determined using the Slovin formula with an error limit of 10%. The interview process uses a proportional simple random sampling technique. The data obtained were then analyzed descriptively quantitatively using a Likert scale. The results showed that there was several activities rehabilitation forest, namely: the planning subsystem with field technical design activities had a final value of 3, the implementation subsystem with a seedling, planting, and plant maintenance activities, with each final value of 3, except for plants which had a final value of 4 Monitoring and evaluation subsystem with monitoring and evaluation activities, with a final score of 3. The Forest and Land Rehabilitation (FLR) activities with community participation levels have Ordinary criteria (B). This shows that forest rehabilitation activities involving farmers are implemented correctly so that the land on which farmers are involved in rehabilitation activities is expected to be more sustainable.